PENGARUH BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL PEMEDIASI PADA PT. BPR SIAGA DANA KUTA - Ni Kadek Desi Arianti; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Organizational Citizenship Behavior or OCB is a profound contribution that exceeds the demands of a role in the workplace and earns awards from companies based on the tasks that have been carried out by Organizational Citizenship Behavior which can arise from various factors in the organization, including due to the organizational culture of employees and high organizational commitment. This study aims to test and obtain empirical evidence of the influence of Organizational Culture and Organizational Commitment on Organizational Citizenship Behavior of PT. BPR Siaga Dana Kuta. The study population was the company at PT BPR Siaga Dana Kuta 1992. The sample in this study was 34 people who were determined based on the simple random sampling method. The analytical tool used to test the hypothesis is the Statistical Package for Social Science. 20. The results showed that organizational culture, organizational commitment have a positive and significant effect on Organizational Citizenship Behavior. Future research that will conduct similar research is expected to influence OCB both interests and talents, work passion, employee character and so on so that there are many factors. possibilities that can affect OCB in a company.